Bacterial ‘immunity’ against bacteriophages - Abedon, Stephen T. (Landes Bioscience, 2012)
Vertebrate animals possess multiple anti-pathogen defenses. Individual mechanisms usually are differentiated into those that are immunologically adaptive vs. more “primitive” anti-pathogen phenomena described as innate responses. Here I frame defenses used by bacteria against bacteriophages as analogous to these animal immune functions. Included are numerous anti-phage defenses in addition to the adaptive immunity associated with CRISPR/cas systems. As these other anti-pathogen mechanisms are non-adaptive they can be described as making up an innate bacterial immunity. This exercise was undertaken in light of the recent excitement over the discovery that CRISPR/cas systems can serve, as noted, as a form of bacterial adaptive immunity. The broader goal, however, is to gain novel insight into bacterial defenses against phages by fitting these mechanisms into considerations of how multicellular organisms also defend themselves against pathogens. This commentary can be viewed in addition as a bid toward integrating these numerous bacterial anti-phage defenses into a more unified immunology.